Phonological processes of modern Guinean - da Anunciação Santos, Natali (2022)
This article analyzes three phonological phenomena of modern Guinean: the palatalization of /s/ in coda and the status of [ʃ] in complex onsets, nasalization by coda and onset, and variation of /r/. The lexical items analyzed were taken from Scantamburlo (2002), inserted in phrases, with phonetics realization confirmed with native speakers. For the context of analysis, we considered: vowel quality, syllabic position and lexical stress. The results indicate that palatalization reaches the coda and complex onset. We attest to tautosyllabic nasalization, unlike heterosyllabic nasalization. Finally, the variation of /r/ reaches the word boundaries: final codas and initial onsets.